2014
DOI: 10.1038/nature13546
|View full text |Cite
|
Sign up to set email alerts
|

A major advance of tropical Andean glaciers during the Antarctic cold reversal

Abstract: The Younger Dryas stadial, a cold event spanning 12,800 to 11,500 years ago, during the last deglaciation, is thought to coincide with the last major glacial re-advance in the tropical Andes. This interpretation relies mainly on cosmic-ray exposure dating of glacial deposits. Recent studies, however, have established new production rates for cosmogenic (10)Be and (3)He, which make it necessary to update all chronologies in this region and revise our understanding of cryospheric responses to climate variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 46 publications
10
112
0
3
Order By: Relevance
“…A reasonable hypothesis would be that the Arid Diagonal would demarcate the boundary of influence between these hemispheric effects, but reviews of glacial chronologies have remained inconclusive on this matter (Ward et al, 2015), with some workers (e.g., Jomelli et al, 2014) suggesting that the timing of glacial advances in tropical South America indicates an influence of the ACR there. Among the sites considered here, only the two northernmost appear to have late glacial positions that could correspond to either the YD or the ACR.…”
Section: Discussionmentioning
confidence: 99%
“…A reasonable hypothesis would be that the Arid Diagonal would demarcate the boundary of influence between these hemispheric effects, but reviews of glacial chronologies have remained inconclusive on this matter (Ward et al, 2015), with some workers (e.g., Jomelli et al, 2014) suggesting that the timing of glacial advances in tropical South America indicates an influence of the ACR there. Among the sites considered here, only the two northernmost appear to have late glacial positions that could correspond to either the YD or the ACR.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014 a paper suggested that tropical glaciers responded very sensitively to the changing climate during the ACR (Jomelli et al, 2014). In this study, we reexamine the conclusions from this study by recalculating previous chronologies based on 226 10 Be and 14 3 He ages respectively, and using the most up-to date production rates for these cosmogenic nuclides in the Tropical Andes.…”
Section: Abstract the Sensitivity Of Tropical Glaciers To Paleoclimamentioning
confidence: 97%
“…In this study, we reexamine the conclusions from this study by recalculating previous chronologies based on 226 10 Be and 14 3 He ages respectively, and using the most up-to date production rates for these cosmogenic nuclides in the Tropical Andes. 53 moraines from 25 glaciers were selected from the previous analysis provided by Jomelli et al (2014) …”
Section: Abstract the Sensitivity Of Tropical Glaciers To Paleoclimamentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of the post-LLGM minor advances is not known. However, it must be noted that in the Sierra Nevada del Cocuy, Colombia (6.5°N), there is evidence of a glacial advance within the Antarctic Cold Reversal (14.5-12.9 ka), followed by a minor advance or stillstand during the late Younger Dryas, the latter in connection with abrupt regional warming (Jomelli et al, 2014).…”
Section: Comparison With Other Glacial and Paleoclimate Recordsmentioning
confidence: 99%